Developing Poetry Writing Teaching Materials Based on Environment and Local Culture for The Fourth Graders - Rosmayanti, Ervi; Supriyanto, Teguh; Sunarso, Ali (Journal of Primary Education)
Learning to write poetry is not only can develop the creativity of writing but can also be used as a means to instill the values of students characters. Learning to write poetry is still less desirable. One of the effort to make writing poetry becomes interesting is to develop its teaching materials. This research has the purpose of developing the teaching materials of poetry writing. Based on the environment and local culture in Kudus in accordance to the needs of teachers and students, to determine the draft, to calculate the validity and acceptability of teaching materials development. Gall and Borg proposed the design of this research with limited scale trial on five students and an elementary school teacher in Kudus. The results showed that the need for teaching materials and forms of teaching materials should consider the appropriateness of content, presentation, linguistic or legibility, and graphics according to the needs of teachers and students. The teaching materials are significantly valid to be used with an average score of 3.33. The acceptance of test results showed that the teaching material to write poems based on the environment and local culture in Kudus for the fourth graders is highly accepted with the acquisition score of 86.6%. A conclusion that the teaching materials developed to meet the criteria for developing teaching materials. The benefits of this research are the availability of teaching materials that can help students in improving the ability to write poetry and to increase the level and the quality of teachers.